Topological Constraint Theory Analysis of Rigidity Transition in Highly Coordinate Amorphous Hydrogenated Boron Carbide - Nordell, Bradley J.; Nguyen, Thuong D.; Caruso, Anthony N.; Lanford, William A.; Henry, Patrick; Li, Han; Ross, Liza L.; King, Sean W.; Paquette, Michelle M. (Frontiers in Materials, 2019)
Topological constraint theory (TCT) has revealed itself to be a powerful tool in interpreting the behaviors of amorphous solids. The theory predicts a transition between a ‘rigid’ overconstrained network and a ‘floppy’ underconstrained network as a function of connectivity or average coordination number, <r>. The predicted results have been shown experimentally for various glassy materials, the majority of these being based on four-fold-coordinate networks such as chalcogenide and oxide glasses. Here, we demonstrate the broader applicability of topological constraint theory to uniquely coordinated amorphous hydrogenated boron carbide (a-BC:H), based on six-fold-coordinate boron atoms arranged into partially hydrogenated interconnected twelve-vertex icosahedra. We have produced a substantial set of plasma-enhanced chemical vapor deposited a-BC:H films with a large range of densities and network coordination, and demonstrate a clear threshold in Young’s modulus as a function of <r>, ascribed to a rigidity transition. We investigate constraint counting strategies in this material and show that by treating icosahedra as ‘superatoms,’ a rigidity transition is observed within the range of the theoretically predicted <r>c value of 2.4 for covalent solids with bond-stretching and bond-bending forces. This experimental data set for a-BC:H is unique in that it represents a uniform change in connectivity with <r> and demonstrates a distinct rigidity transition with data points both above and below the transition threshold. Finally, we discuss how TCT can be applied to explain and optimize mechanical and dielectric properties in a-BC:H and related materials in the context of microelectronics applications.